2020
DOI: 10.1093/bjs/znaa013
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of multimodal analgesia with thoracic epidural after transthoracic oesophagectomy

Abstract: Background Thoracic epidural analgesia (TEA) has been regarded as the standard of care after oesophagectomy for pain control, but has several side-effects. Multimodal (intrathecal diamorphine, paravertebral and rectus sheath catheters) analgesia (MA) may facilitate postoperative mobilization by reducing hypotensive episodes and the need for vasopressors, but uncertainty exists about whether it provides comparable analgesia. This study aimed to determine whether MA provides comparable analgesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Several studies have shown comparable postoperative pain management in MIS procedures and open abdominal surgery using the transversus abdominal plane block [ [22] , [23] , [24] ]. Recently, Ng Cheong Chung et al have shown that a multimodal approach including intrathecal morphine, paravertebral and rectus sheath block provides comparable analgesia to thoracic EA in transthoracic oesophagectomy [ 25 ]. A meta-analysis of 29 randomized controlled trials, including 2059 patients, demonstrated that postoperative pain control after abdominal surgery is comparable to epidural analgesia when pre-peritoneal wound catheters are used.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown comparable postoperative pain management in MIS procedures and open abdominal surgery using the transversus abdominal plane block [ [22] , [23] , [24] ]. Recently, Ng Cheong Chung et al have shown that a multimodal approach including intrathecal morphine, paravertebral and rectus sheath block provides comparable analgesia to thoracic EA in transthoracic oesophagectomy [ 25 ]. A meta-analysis of 29 randomized controlled trials, including 2059 patients, demonstrated that postoperative pain control after abdominal surgery is comparable to epidural analgesia when pre-peritoneal wound catheters are used.…”
Section: Discussionmentioning
confidence: 99%
“…There are several factors that may have contributed toward improved outcomes, although it is impossible to establish a direct cause and effect relationship. The integration of a standardized enhanced recovery pathway, may have served to ensure uniform care for patients, with a standardized analgesic regime (which has dispensed with epidurals and now favors rectus sheath catheters, and patient controlled analgesia as well as intrathecal diamorphine at induction), 22,23 early mobilization and a uniform approach to nutrition. This multimodal analgesic regime, without epidural, reduces the incidence hypotension, which can limit a patients' ability to mobilize, and may have contributed toward the reduction in pulmonary complications.…”
Section: Discussionmentioning
confidence: 99%